Clinical Features and Principles of Differential Diagnosis of Erysipelas - S. D. Shapoval; L. A. Vasylevska; V. O. Bielinska (Сучасні медичні технології)
Purpose. The purpose is to find out the common and different features of the clinical course of erysipelas from other diseases that can imitate it. Materials and methods. 114 case histories of patients who were hospitalized in the center of purulent-septic surgery in the Non-profit municipal enterprise “City Hospital № 3” in Zaporizhzhia for the period 2019-2020 were analyzed. 123 patients, who underwent hospital treatment in the center during this period of time, were with post-injection abscesses of soft tissue, 184 - with soft tissue abscesses, 203 - with phlegmons of various localizations, 49 - with complicated panaritium, 3 of which -  subcutaneous. Over the past 5 years, 127 patients were consulted in the clinic and other therapeutic, infectious, neurological and other departments of the city. A number of criteria and signs have been identified to differentiate erysipelas from diseases that may have similar clinical symptoms and a number of circumstances that need to be clarified. Results. It is established that the diagnosis of erysipelas does not require special laboratory examination and is made on the basis of examination of the patient, epidemiological history and medical history. Provoking factors in the development of erysipelas are: violation of the integrity of the skin (abrasions, scratches, abrasions, cracks, bruises, injuries); mycoses; a sharp change in temperature (supercooling, overheating); emotional stress; increased insolation. Erysipelas has a characteristic summer-autumn seasonality. In people engaged in physical labor, the disease is registered more often than in other types of work. Hereditary predisposition to the disease is observed in 10-15% of cases. In this regard,  the presence of such factors as congenital and acquired venous insufficiency of the lower extremities, fungal infection of the lower extremities, the presence of postoperative and post-traumatic scars, lymphostasis, diabetes, cardiovascular disease and diseases accompanied by the development of edema, intake of corticosteroids or cytostatics are of essential significance in the development of the disease.